Predictors of Omphalitis among Spontaneous Vertex Delivery Neonates in Nakuru County Hospital, Kenya (International Journal of Scientific Research and Management (IJSRM), 2020)
Background; Omphalitis (umbilical cord infection) among new-borns is common and a major cause of neonatal deaths in developing countries. Annually, about 4 million neonatal deaths occur around the world. Of these, >30% are caused by infections that mainly from umbilical cord. Cord care practices may directly contribute neonatal infections, largely contributing tothis was part data from a larger randomized trial among 540 participant’s neonatal deaths. Cord infections are more prevalent in developing countries because of the high rates of poverty and unhygienic practices. Objective: To determine the predictors of omphalitis among neonates in Nakuru County Hospital, Kenya. Methodology This was part data from a larger randomized trial among 540 participants. Findings: The prevalence of Omphalitis was 23.1. Babies whose mothers’ did not wash hands when eating had 2.14 times risk of developing cord infection compared to those babies whose mothers’ indicated otherwise [AOR=2.14; 95%CI=1.28 - 3.57; p=0.004]. Likewise, babies whose mothers’ never folded diapers backwards were twice likely over those who did to develop cord infection [AOR=1.88; 95%CI=1.03 - 3.44; p=0.039]. Babies whose mothers’ stayed in different rooms had 7.35 times risk of developing cord infection [AOR=7.35; 95%CI=3.40 - 15.91; p<0.001] over those roomed in. Conclusion and recommendation: Maternal and caretakers hand hygiene, folding back of diapers and rooming in are critical in cord infection prevention. Health education to mothers and care takers on the importance of hand hygiene, diaper application and importance of rooming in is recommended to minimise omphalitis and consequential morbidity.